Rancang Bangun Interkoneksi Jaringan Berbasis VPN Menggunakan Metode EOIP Tunnel - Verian Nugroho, Dimas; Noprisson, Handrie (JSAI (Journal Scientific and Applied Informatics), 2024)
This research aims to solve the problem of automatic data backup between the server at the Cyber ​​Data Center and the server at the XYZ Apartment using Ethernet over IP (EoIP) Tunnel technology on the MikroTik network. The main problem faced is that there is no direct path to connect the two servers, so the data synchronization and backup process must be done manually. Experimental research methods using the Network Development Life Cycle (NDLC) approach are used to analyze needs, design new networks, implement and evaluate the designed solutions. EoIP Tunnel implementation is carried out to create an exclusive and secure communication path, equipped with static route configuration and automatic robocopy-based scripts to support regular data backup. Connectivity testing shows optimal results with a stable transfer speed of 49 Mbps, without problems in sending files from the AST server to the QNAP server.